2018
DOI: 10.1016/j.jmb.2018.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Glycomics and Proteomics Approaches to Investigate Early Adenovirus–Host Cell Interactions

Abstract: Adenoviruses as most viruses rely on glycan and protein interactions to attach to and enter susceptible host cells. The Adenoviridae family comprises more than 80 human types and they differ in their attachment factor and receptor usage, which likely contributes to the diverse tropism of the different types. In the past years, methods to systematically identify glycan and protein interactions have advanced. In particular sensitivity, speed and coverage of mass spectrometric analyses allow for high-throughput i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 182 publications
(206 reference statements)
1
22
0
Order By: Relevance
“…Other techniques have been used to identify relevant genes and inflammatory markers. Studies performed to date have evaluated the microbiota of EPL using culture [ 31 , 111 , 112 ] and have employed targeted molecular techniques including polymerase chain reaction (PCR) [ 30 , 31 , 36 , 38 ], real-time PCR [ 32 ] and checkerboard DNA–DNA hybridization [ 107 , 113 ], open-ended molecular techniques (next generation sequencing; NGS) [ 37 ] and denaturing gradient gel electrophoresis (DGGE) and/or gene cloning and sequencing [ 36 , 38 ]. Overall, these studies revealed significant similarities between the microbiota found in the root canals and those in periodontal pockets.…”
Section: Outlook For the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Other techniques have been used to identify relevant genes and inflammatory markers. Studies performed to date have evaluated the microbiota of EPL using culture [ 31 , 111 , 112 ] and have employed targeted molecular techniques including polymerase chain reaction (PCR) [ 30 , 31 , 36 , 38 ], real-time PCR [ 32 ] and checkerboard DNA–DNA hybridization [ 107 , 113 ], open-ended molecular techniques (next generation sequencing; NGS) [ 37 ] and denaturing gradient gel electrophoresis (DGGE) and/or gene cloning and sequencing [ 36 , 38 ]. Overall, these studies revealed significant similarities between the microbiota found in the root canals and those in periodontal pockets.…”
Section: Outlook For the Futurementioning
confidence: 99%
“…Overall, these studies revealed significant similarities between the microbiota found in the root canals and those in periodontal pockets. Furthermore, developments in glycan microarray technologies have led to targeted identification of glycan-based receptors [ 113 ]. The mapping of cell surface interactions of the diverse types of adenovirus has implications for cells, tissues, and other structures, as well as for drug development.…”
Section: Outlook For the Futurementioning
confidence: 99%
“…Virus entry, as other life cycle steps, is coordinated by protein-protein networks of the host cell, which may be hijacked and/or modified by viruses (Prusty et al 2014;Gerold et al 2015;Viswanathan et al 2017;Bruening et al 2018;Scaturro et al 2018). Technological advances, in particular in interaction shotgun proteomics, allow the systematic analysis of protein interactions during virus entry and the construction of a systems biology view of the entry process (Damm and Pelkmans 2006;Walther and Mann 2010;Cox and Mann 2011;Shah et al 2015;Gerold et al 2016Gerold et al , 2017Lasswitz et al 2018). Although alternative methods such as high throughput imaging and integrative analysis of RNA interference, haploid cell screens, and CRISPR knockout screens can provide indirect evidence on engaged protein networks (Damm and Pelkmans 2006;Park et al 2013;Kilcher and Mercer 2014), we will in the following focus on evidence based on proteomic analyses of host networks engaged during HCV invasion.…”
Section: Protein-protein Interactions During Hcv Entry: Toward a Systmentioning
confidence: 99%
“…In contrast to the previously described genomic approaches, interactome and proteomics aim to directly identify the protein-protein interactions (PPIs), which occur between virus attachment proteins and their host receptors. Historically, [83] this has been performed using virus overlay protein binding assays (VOPBA) (reviewed in [102]). Although VOPBA have successfully identified receptors for several viruses, including lymphocytic choriomeningitis virus and lassa virus [78], VOPBA suffer from several problems.…”
Section: Interactomics and Proteomicsmentioning
confidence: 99%